2009
DOI: 10.1016/j.mineng.2009.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Inferential measurement of SAG mill parameters V: MPC simulation

Abstract: This paper discusses a case study application of inferential measurement models for semiautogenous grinding (SAG)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Substituting the common formula of circular motion v = π rn 30 into (8), the relation between the radical position and the charge shoulder angle is given by…”
Section: Power Drawmentioning
confidence: 99%
See 1 more Smart Citation
“…Substituting the common formula of circular motion v = π rn 30 into (8), the relation between the radical position and the charge shoulder angle is given by…”
Section: Power Drawmentioning
confidence: 99%
“…Apelt et al made enormous contributions to the model and control for the SAG mill [3]- [6]. Considering the feed ore size distribution, Amestica et al presented a dynamic model by taking the masses of water, copper rocks and granules as state variables [7], [8]. In [9], the control model was developed with taking the delivery rate of copper rocks, the feed flow rate of water and the rotation speed as control inputs and considering the power, the filling rate and particle size reduction as output variables.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of the fractional order controllers to control the grinding mill circuit is compared to the performance of an LMPC controller. LMPC is chosen as it can be considered to be the de-facto standard for advanced process control implementations in industry [51,52], and was successfully applied to control grinding mill circuits both in simulation and practice [1,2,3,53,54]. The aim of the LMPC controller can be described as: min…”
Section: Lmpc Controllermentioning
confidence: 99%
“…The economic performance of PID control compared to nonlinear MPC when applied to a grinding mill circuit was evaluated by Wei and Craig [9] and results showed that nonlinear MPC (NMPC) can improve performance with respect to recovered mineral value in downstream flotation circuits. Further improvements to overall MPC performance can be achieved by incorporating peripheral control tools such as inferential measurements, disturbance observers or model-plant mismatch detection [10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [3], Niemi et al [5], Pomerleau et al [6], Ramasamy et al [7], Remes et al [8], Apelt and Thornhill [11], Yang et al [12],Chen et al [14]. Because of the highly nonlinear nature of a grinding process, the use of NMPC with fundamental nonlinear models is more desireable.…”
Section: Introductionmentioning
confidence: 99%